Desarrollo de un plástico biodegradable por medio de la microalga Chlorella vulgaris cultivada en aguas residuales industriales. (2022)
Due to the impact generated by wastewater to the environment, the use of these for the cultivation of microalgae is sought, since they have a large amount of nutrients that allow their growth, which is why the use of these wastes for the cultivation of microalgae is proposed. production of a biopolymer through the microalgae Chlorella vulgaris which can replace oil-derived plastics in order to reduce the damage generated to the environment. Three different industrial wastewaters belonging to the poultry, flower and dairy sectors were evaluated by means of decision matrices proposed by the hierarchical analysis method, where it was obtained that the best industry corresponds to the dairy industry. Subsequently, a bibliometric review was carried out using the Scopus database and the Bibliometrix software, in order to present the most used methodology in obtaining the bioplastic (polyhydroxyalkanoate), showing that the technique adapted by various authors for the extraction of PHA is the chloroform method, allowing a yield of 13.24% of the bioplastic to be obtained with respect to the microalgal biomass.